Constitutional and legislative regulation for the seat vacancy of the member of the House of Representative in Iraq - محمود, ختام حمادي (Journal of Legal Sciences, 2019)
Our research, entitled "The constitutional and legal regulation of the vacancy of the seat of the member of the House of Representatives in Iraq", to study the most important reasons it follows the vacancy of the seat and the ways filling it , belief in the importance of this subject because the MP represents the entire people and exercises many powers In which you notice will electorate and their ambitions, so this study focused on the statement of the constitutional and legal organization of the reasons that result in the vacancy , And the way adopted in filling vacant parliamentary seats according to Article (49) of the Constitution of Iraq for the year 2005 and the law of the elections of members of the House of Representatives for 2013 and the law of replacement of members of the House of Representatives No. 6 of 2006 and the rules of procedure of the House of Representatives for 2006, It became clear through the study that there are many gaps and flaws in the texts organized by this subject as well as the existence of many confidation and inconsistencies between those laws .